LncRNA Rpph1 protects amyloid-β induced neuronal injury in SK-N-SH cells via miR-122/Wnt1 axis. (3rd May 2020) - Gu, Ran; Wang, Lu; Tang, Man; Li, Shi-Rong; Liu, Rui; Hu, Xiao
Abstract: Objective: To investigate the role of lncRNA Rpph1 on amyloid-β induced neuronal injury in SK-N-SH cells and underlying mechanism. Methods: In vitro Alzheimer's disease (AD) model was established using the SK-N-SH cells treated with Aβ25-35 peptide. APPswe/PS1ΔE9 double transgenic mice were used as AD animal model. Rpph1 was over-expressed and miR-122 was inhibited or overexpressed in SK-N-SH cells via transfection with pcDNA3.1-oe Rpph1 vector, miR-122 inhibitor or miR-122 mimic, respectively. Cell viabilities and apoptosis were evaluated using MTT or flow cytometry assay, respectively. Quantitative real-time PCR (RT-qPCR) was used to determine expression of Rpph1 and miR-122. Western blotting was used to determine the expression of apoptosis related proteins as well as Wnt/β-catenin signaling related proteins. Dual luciferase reporter assay was conducted to confirm the binding of miR-122 with predictive binding site in 3' UTR of Rpph1 and Wnt1. Results: Both lncRNA Rpph1 and miR-122 were up-regulated in AD mouse. Either over-expression of Rpph1 or inhibition of miR-122 restored the cell viability or decreased cell apoptosis rate in Aβ induced SK-N-SH cells. Overexpression of miR-122 inhibited the cell viability while did not influence the Aβ level in SK-N-SH cells. Furthermore, over-expression of Rpph1, as well as inhibition of miR-122, elevated Bcl-2, c-myc, Survivin and decreased Bax expression via activating Wnt/β-catenin signaling. Dual luciferase reporter assay showed that miR-122 could directly target to 3'UTR of Rpph1 and Wnt1. Conclusion: Both lncRNA Rpph1 and miR-122 were up-regulated in AD mouse and Rpph1 activated Wnt/β-catenin signaling to ameliorate amyloid-β induced neuronal apoptosis in SK-N-SH cells via direct targeting miR-122.